Seismic behaviour of steel-reinforced ultra-high-strength concrete composite frame: Experimental study. Issue 9 (July 2019) - Zhang, Jiancheng; Jia, Jinqing; Yu, Jing; Sun, Zhen
This article provides the results of an experimental study on the seismic behaviour of the steel-reinforced ultra-high-strength concrete frame. A two-bay and three-story one-fourth scale steel-reinforced ultra-high-strength concrete frame specimen was tested under simulated earthquake loading conditions. The seismic behaviours of the specimen, including the failure mode, concrete element cracks development, hysteresis loops, lateral load-carrying capacity, ductility, energy dissipation, strength and stiffness degradation, were investigated under low reversed cyclic lateral loading. The test results showed that the beam hinge failure mechanism of the steel-reinforced ultra-high-strength concrete frame was achieved. The steel-reinforced ultra-high-strength concrete frame would have rich and stable hysteretic loops when subjected to large axial load with an axial load ratio of 0.38. The roof and interstory ductility coefficients of the steel-reinforced ultra-high-strength concrete frame ranged from 5.06 to 6.78. The strength and stiffness degenerated gradually, indicating an excellent seismic behaviour of the steel-reinforced ultra-high-strength concrete frame with sufficient ductility and high energy dissipation capacity. The test and analysis results can be served as a design reference for practical engineering applications.